Physiologically based pharmacokinetic model of lapatinib developed in mice and scaled to humans - Hudachek, Susan F.; Gustafson, Daniel L. (Journal of pharmacokinetics and pharmacodynamics, 2013)
Lapatinib is an oral 4-anilinoquinazoline derivative that dually inhibits epidermal growth factor receptor and human epidermal growth factor receptor 2 (HER2). This drug is a mere decade old and has only been approved by the FDA for the treatment of breast cancer since 2007. Consequently, the intricacies of the pharmacokinetics are still being elucidated. In the work presented herein, we determined the biodistribution of orally administered lapatinib in mouse plasma, brain, heart, lung, kidney, intestine, liver, muscle and adipose tissue. Using this data, we subsequently developed a physiologically based pharmacokinetic (PBPK) model of lapatinib in mice that accurately predicted the tissue concentrations after doses of 30, 60 and 90 mg/kg. By taking into account interspecies differences in physiology and physiochemistry, we then extrapolated the mouse PBPK model to humans. Our model predictions closely reflected lapatinib plasma pharmacokinetics in healthy subjects. Additionally, we were also able to simulate the pharmacokinetics of this drug in the plasma of patients with solid malignancies by incorporating a decrease in liver metabolism into the model. Finally, our PBPK model also facilitated the estimation of various human tissue exposures to lapatinib, which harmonize with the organ-specific toxicities observed in clinical trials. This first-generation PBPK model of lapatinib can be further improved with a greater understanding of lapatinib absorption, distribution, metabolism and excretion garnered from subsequent in vitro and in vivo studies and expanded to include other pharmacokinetic determinants, including efflux transporters, metabolite generation, combination dosing, etc., to better predict lapatinib disposition in both mouse and man.